Topological Alterations of Working Memory Impairment in Aged Patients With Vascular Dementia - Zheng, Cao; Zhang, Rong-Sheng; Wan, Ting; Zhao, Jun-Sheng (Frontiers in Aging Neuroscience, 2021)
Aneurysmal subarachnoid hemorrhage (aSAH) is a common cause of vascular dementia in aged patients. Survivors often experience cognitive impairments, especially working memory deficits. Currently, the lack of a theoretical framework for describing these changes limits the development of cognitive interventions or rehabilitation. It is unclear how the large-scale network differs and the extent to which the brain network is affected in these patients. Here, we examined the topological characteristics of brain organization, especially the ‘small-world’ properties, in 62 aged aSAH patients. The participants were divided into two groups according to whether they exhibited working memory deficits. Cognitive function including working memory was evaluated using the TMT-B and AVLT (Chinese version), and functional magnetic resonance imaging was performed to measure resting-state cortical plasticity. We used independent component analysis to extract functional sub-networks including working memory networks from imaging data. Then, we established binarized networks and calculated the small-worldness properties, as well as the local and global efficiency of the networks. Clustering coefficients did not significantly vary between aSAH patients with working memory deficits and controls. However, we found a significant decrease in the characteristic path length in aSAH patients with working memory deficits, indicating an increase in overall routing efficiency. These patients may have to recruit more neuronal resources during daily cognitive activity, leading to higher overall routing efficiency of the local network. This study provides novel information regarding neural changes in aSAH patients with working memory deficits, and contributes to our understanding of the neural mechanisms of vascular dementia, which may facilitate improved interventions.